Anammox biofilter with denitrification sludge as seed in treating low nitrogen strength wastewater. (15th December 2022) - Li, Gaigai; Wang, Jinxing; Ning, Dingying; Chen, Bingquan; Liu, Jia; Jin, Deyuan; Guo, Wuke; Liang, Jidong; Ji, Hua
Abstract: Deficient seed sludge, low substrate concentrations are recognized as the major barriers for the application of anaerobic ammonia oxidation (Anammox) to treat mainstream wastewater. In this work, anammox biofilter (A-BF) was started up by inoculating denitrification sludge at low nitrogen strength at 25 °C. The total nitrogen removal efficiency (TNRE) and nitrogen removal rate (NRR) reached 74.8 ± 3.4% and 0.81 kg-N m −3 d −1 under nitrogen loading rate (NLR) of 1.20 kg-N m −3 d −1 with 7.00 mg-NH4 + -N L −1 and 10.00 mg-NO2 - -N L −1 as influent. 1.00–2.00 mg-DO L −1 negatively impacted effluent, but the total nitrogen of effluent (TNeff ) was 10.65 ± 2.76 mg L −1, in limit of the standard of Class 1A for municipal WWTP discharge (GB18918-2002). The abundance of Planctomycetes increased from 0.6% to 1.4–2.6%, in which, Candidatus_Brocadia was the dominant genera. The results establish the application feasibility of A-BFs as advanced nitrogen removal technique in treating mainstream wastewater. Highlights: A-BF was started up by inoculating denitrification sludge at low nitrogen strength. 63.3 ± 7.1% of TNRE was achieved with 7 mg-NH4 + -N·L −1 and 10 mg-NO2 - -N·L −1 as influent. TNRE and NRR achieved 74.8 ± 3.4% and 0.81 kg-N m −3 d −1 under NLR of 1.20 kg-N m −3 d −1 . 1-2 mg-DO L −1 negatively impacted TNeff, but which kept in less than 15 mg-TN L −1 . Candidatus_Brocadia was domesticated as the dominant AnAOB in this study.